Socioeconomic profiles of timber consumers in the buffer zones of Bu Gia Map National Park, Vietnam. (10th March 2021) - Nguyen, Toai; Lawler, Susan; Paul, Warren
Summary: People who live on the edges of protected areas may harvest timber to make their living from this natural forest product. Therefore, understanding timber consumption at the household level is critical for developing effective conservation policies. Previous studies have highlighted relationships between the consumption of forest products and socioeconomic status, but they have failed to examine timber consumption under cultural contexts. In this study, we interviewed 121 villagers to examine the socioeconomic profiles of timber consumers with regards to their indigenous culture in the buffer zones of Vietnam's Bu Gia Map National Park. We found that indigenous identity, landownership, number of crops grown by villagers and proximity to markets are statistically significant for explaining the consumption of timber from natural forests. Given the high likelihood that most of this timber was collected illegally, we make several recommendations for forest managers on how to interact with villagers to improve park protection.